Eye Gnat (Liohippelates, Diptera: Chloropidae) Biology, Ecology, and Management: Past, Present, and future. Issue 1 (11th July 2022) - Klepzig, Kier D; Hartshorn, Jessica A; Tsalickis, Alexandra; Sheehan, Thomas N
Abstract: Eye gnats (mainly Liohippelates pusio and Liohippelates collusor ) are pest species that have been the subject of considerable research and extension activity in the United States since the 1930s. They cause considerable discomfort and stress—and may transmit pathogens—to humans and animals. We reviewed the abundant literature on biological, ecological, and management aspects of Liohippelates eye gnats. Eye gnat biology and life cycles have been well studied in agricultural systems. However, their ecology, roles in trophic cascades, and functions in natural ecosystems, particularly forests, are not well documented. Additionally, there remain opportunities to improve traps, repellents, deterrents, and controls for eye gnats. The substantial and substantive early work on these insects provides a strong foundation for future investigations and extension.